‫علاقة‬‫ التعلم‬ ‫التنظيمي‬ ‫برأس‬ ‫المال‬ ‫الفكري‬ ‫دراسة ‬‫حالة‬ الصندوق‬ ‫الوطني‬ ‫للضمان‬ الإجتماعي‬ ‫س‪/‬ه‬ - خلود ‫جبيلي‬‫ ‬; ‬‫اميرة‫ جعفري ‬ (My University, 2018)
The aim of this study is to find the relationship between two basic variables, the first being independent, organizational learning and the second is intellectual capital. The main objective of organizational learning is the continuous development of organizational knowledge, It is a group of processes that seek to acquire and disseminateknowledge among the members of the Organization to achieve the greatest organizational effectiveness that contributes to the development of the human element, which directly affects the development of intellectual capital and its support by the Organization to create new and diverse ideas that work towards achieving the objectives of the Organization. Finally, we presented the effect of organizational learning on intellectual capital by studying a random sample of employees of the Social Security Fund in the state of Souk Ahras. In this study, we used the analytical descriptive approach. We found that organizational learning has a direct and significant impact on the influence and development of intellectual capital. ...................................................................... هدف هذه الدراسة إلى إيجاد العلاقة بين متغيرين أساسيين، الأول هو التعلم التنظيمي المستقل والثاني هو رأس المال الفكري. الهدف الرئيسي التعلم التنظيمي هو التطوير المستمر للمعرفة التنظيمية، وهو مجموعة من العمليات التي تسعى إلى اكتساب ونشر المعرفة بين أعضاء المجموعة المنظمة لتحقيق أكبر قدر من الفعالية التنظيمية التي تساهم في تنمية العنصر البشري مما يؤثر بشكل مباشر على التطور الفكري رأس المال ودعمه من قبل المنظمة لخلق أفكار جديدة ومتنوعة تعمل على تحقيقها تحقيق أهداف المنظمة. وأخيراً عرضنا أثر التعلم التنظيمي على رأس المال الفكري من خلال دراسة أ عينة عشوائية من موظفي صندوق الضمان الاجتماعي بولاية سوق أهراس. واستخدمنا في هذه الدراسة المنهج الوصفي التحليلي. وجدنا أن التنظيمية إن التعلم له تأثير مباشر وكبير على التأثير والتطور الفكري عاصمة.